Correlação entre o consumo alimentar e o nível sanguíneo de potássio e fósforo em nefropatas hemodialíticos em um centro de referência em nefrologia em Belém do Pará - SOUZA, Adriane Fonseca de (2023)
Introduction: Hyperkalaemia and hyperphosphatemia are electrolyte imbalances commonly diagnosed in chronic kidney patients, originating from both food and other factors, with a risk of death if there is no proper control. Objective: To identify whether food influences the hyperkalemic and hyperphosphatemic conditions of chronic renal patients. Methodology: Qualitative, quantitative, crosssectional, prospective and descriptive study with 65 patients from the Hemodialysis Center Monteiro Leite. Where, data collection was carried out from a questionnaire on epidemiological, socioeconomic, sociodemographic and biochemical issues; in addition to the analysis of food consumption made with the application of the food frequency questionnaire and three 24hour reminders, with the approval of the Ethics and Research Committee under opinion Nº 2.970.945. Results: It was identified that the majority of the population belonged to the male gender and adulthood, with major diagnoses of hypertensive nephrosclerosis and diabetic nephropathy, with prevalence for treatment of 15 years and individual and family income of 12 minimum wages, significant percentage for incomplete elementary education, naturalness with percentages close to capital and interior and high provenance for capital. In the intake of potassium the majority is below and of phosphorus a relevant amount above the recommended. Still, there was a predominance of normocalemia and hyperphosphatemia, with correlations with ingestions: nonsignificant weak and significant weak, respectively. Conclusion: In this way, it is concluded that food intake can influence the potassium and phosphorus elevation conditions, however it is not the only nor the main cause of the studied hydroelectrolytic changes.